Cultura de compartilhamento do conhecimento na gestão de pessoas em instituição de ensino superior - Campos, Ilka Maria Soares (2022)
Knowledge in a contemporary approach has been studied and recognized as a driving force in the development of organizations, since its sharing can exponentially increase the capacity for individual and collective knowledge. It aims to analyze cultural traits of knowledge sharing as an organizational strategy in a higher education institution. In the methodological course, the research is characterized as exploratory and descriptive, with a quantitative and qualitative approach, of the documentary and field type, making use of the case study method at the Dean of Personnel Management at the Federal University of Paraíba. It adopts as instruments and techniques for data collection the questionnaire, document analysis, focus group interview and direct observation. From the universe of 143 civil servants, an intentional sample with 18 managers was adopted. For data analysis, it adopts the association through the triangulation of the interpretive method and Bardin's content analysis, with the categories and subcategories formed from parameters of the knowledge sharing models of the authors Ipê, Tonet and Paz. The identified knowledge sharing culture traits were analyzed from five categories: nature of knowledge, motivate to share, opportunities to share, culture to share and recipient of knowledge. With the results from the subcategories analyzed, it appears that the field of study, even without formally identifying actions and guidelines to promote a culture for sharing knowledge, demonstrates traits of culture for sharing knowledge in part of the work units. It is believed that the gaps identified in the field of study can be minimized with the proposal of innovative strategies for sharing knowledge based on cultural traits in the environments of the Dean's Office for people management. The results allow us to conclude with the validation of the assumptions that the sharing of knowledge as recommended by the literature on knowledge management is not yet evidenced in the Pro-Rectory of people management, so that they can characterize the existence of an adequate organizational culture. As well as the possibly existing incidences of knowledge sharing are not yet characterized as conducive to the theoretical and practical teachings of organizational, informational and knowledge culture proposed in the literature in the area. As a contribution, certainly, the innovative strategies for sharing knowledge that were identified and the proposals based on perceived cultural traits and those that are not evidenced in the people management environment of the field under study, made it possible to propose appropriate indicators for the culture of sharing. for the construction of theory grounded in the factual reality of data and in the area of Information Science.